Does subsidizing legume seeds improve farm productivity and nutrition in Malawi?. (November 2022) - Khonje, Makaiko G.; Nyondo, Christone; Mangisoni, Julius H.; Ricker-Gilbert, Jacob; Burke, William J.; Chadza, William; Muyanga, Milu
Highlights: While farm input subsidies are popular, its effect on nutrition is unknown. Effects of subsidizing legume seeds (SLS) on productivity and nutrition are analyzed. We use panel regression models with instrumental variable approach. SLS improves farm productivity, micronutrient consumption, and child nutrition. Input subsidies for nutrient-dense crops could be key to address malnutrition. Abstract: Over the last two decades, most African governments have been implementing agricultural input subsidy programs (ISPs) aimed at increasing crop yields, and incomes, and reducing hunger, nutritional insecurity, and poverty. Although ISPs are popular policy interventions, it remains unknown whether they improve the productivity of nutrient-dense crops such as legumes, dietary quality, and child or adolescent nutrition. We address this gap by testing the hypothesis that subsidizing legume seeds (SLS) improves farm productivity, dietary quality, and child or adolescent nutrition. To do this, we use decade-long nationally representative panel data from Malawi and panel regression models with an instrumental variable approach to address endogeneity. We found that SLS increases area planted with legume crops, groundnut yield, gross value of crop production, along with production and consumption (dietary) diversity, calories, and micronutrient—vitamin A and zinc—consumption. We further found that SLS is positively correlated with child or adolescent weight-for-age Z-score but not height-for-age Z-score. These novel findings emphasize that SLS could be among the key policy interventions to address malnutrition in the Malawian small farm sector.